Establishing a baseline to measure change in political will and the use of data for decision‐making in maternal and newborn health in six African countries. Issue 1 (16th July 2014) - Nove, Andrea; Hulton, Louise; Martin‐Hilber, Adriane; Matthews, Zoe
Abstract: The Evidence for Action (E4A) program assumes that both resource allocation and quality of care can improve via a strategy that combines evidence and advocacy to stimulate accountability. The present paper explains the methods used to collect baseline monitoring data using two tools developed to inform program design in six focus countries. The first tool is designed to understand the extent to which decision‐makers have access to the data they need, when they need it, and in meaningful formats, and then to use the data to prioritize, plan, and allocate resources. The second tool seeks the views of people working in the area of maternal and newborn health (MNH) about political will, including: quality of care, the political and financial priority accorded to MNH, and the extent to which MNH decision‐makers are accountable to service users. Findings indicate significant potential to improve access to and use of data for decision‐making, particularly at subnational levels. Respondents across all six program countries reported lack of access by ordinary citizens to information on the health and MNH budget, and data on MNH outcomes. In all six countries there was a perceived inequity in the distribution of resources and a perception that politicians do not fully understand the priorities of their constituents.